Using Genre Based Approach To Enhance the Students Writing Skill at MAN 4 BOne - Andi Badania Tenri Waji; St. Asriati; Maharida Manindar (FKIP Unismuh Makassar, 2023)
This study sought to ascertain whether using a genre-based approach while teaching tenth-grade MAN 4 BONE students to write improved their writing abilities in terms of organization and substance. Data were gathered by administering pre-tests, treatments, and post-tests as part of the researcher's pre-experimental approach with a one group pre-test post-test design. 33 students from the X class of MAN 4 BONE made up the research sample.95 pupils from MAN 4 BONE's first grade class made up the study's population. To choose the sample for the study, the cluster sampling technique was used. The method utilized to collect the data was writing ability.The study's findings demonstrate that the students' post-test mean score of 64.39 for content is greater than their pre-test mean score of 45.15. Students' average grade Pre-test scores of 41.61 and 71.36 demonstrate organization, while the hypothesis t-test scores for both content and organization were 2.88 and 3.31, respectively. It denotes Ha's acceptance. based on the discovery that the results of the pre- and post-test differ significantly. A genre-based approach is excellent for improving pupils' writing abilities in terms of structure and substance.